О стандартах доказательства - Тягло, А. В.; Tiaglo, O. V.; ORCID: http://orcid.org/0000-0003-0721-1153; Тягло, О. В. (Форум права. - 2018. - № 1. – С.88- 94, 2018)
Выполнено компаративное исследование стандартов доказательства, принятых в общей логике и в юриспруденции, а соответственно – в юридической логике. С этой целью проанализировано наследие Аристотеля, Г.В. Лейбница, Ч. Беккариа, А.Т. Деннинга и др. Показано, что в юриспруденции общелогический стандарт доказательства следует признать необходимым, но не достаточным. Поэтому здесь необходимо привлечение дополнительных юридических стандартов, например стандарта «вне разумного сомнения». В отличие от общелогического, принятые в юриспруденции стандарты доказательства имеют вероятностную природу. Предложены возможности гармонизации действующего законодательства, требуемой введением в Уголовный процессуальный кодекс Украины операции доказательства вне разумного сомнения.

This paper lies in the general framework of the argumentation that especial legal logic – as one of a set of material logics – exists side by side with general, or formal, logic. In other words, in general case legal logic is not reducible to the use of formal logic in legal reasoning. This position has received some support in few previous publications already. In this paper, a comparative analysis of the standards of proof that take place in general logic and in jurisprudence and, therefore, in legal logic is fulfilled. To understand the standard of proof accepted in general logic, it is natural to address, first of all, Aristotle’s intellectual heritage. Relevant ideas of Gottfried Wilhelm Leibniz and Cesare Beccaria are analyzed further. The standard "beyond a reasonable doubt" is studied as one of the accepted in jurisprudence (Alfred Thompson Denning et al.). The final conclusion is that the standards of proof in general logic and in legal logic differ significantly. The general logic standard of proof should be recognized as necessary, but not sufficient in jurisprudence. This standard is necessary, in particular, in proving the probabilities of competing conclusions, but a substantiated choice of one of them requires a special legal standard additionally: in this regard, are known standards of moral certainty and proof beyond reasonable doubt, preponderance in evidence... It is pointed out, the urgency of consideration of the standard "beyond a reasonable doubt" for our domestic specialists is because it appeared in the Ukrainian legislation just a few years ago – in the Criminal Procedural Code of 2012. It has been borrowed from the Anglo-American legal system. In my opinion, this important innovation demands harmonization of current legislatio.

Виконане компаративне дослідження стандартів доведення, прийнятих у загальній логіці й у юриспруденції, а відповідно – в юридичній логіці. Задля цього проаналізовано спадщину Аристотеля, Г.В. Ляйбниця, Ч. Беккаріа, А.Т. Деннінга та ін. Показано, що в юриспруденції загальнологічний стандарт доведення слід визнати необхідним, але не достатнім. Тому тут потрібне залучення додаткових юридичних стандартів, наприклад стандарту «поза розумним сумнівом». На відміну від загальнологічного, прийняті в юриспруденції стандарти доведення мають ймовірнісну природу. Запропоновані можливості гармонізації чинного законодавства, потрібної внаслідок уведення до Кримінального процесуального кодексу України операції доведення поза розумним сумнівом.
About Standards of Proof
Про стандарти доведення
Тягло, А. В. О стандартах доказательства [Електронний ресурс] / А. В. Тягло // Форум права. - 2018. - № 1. С. 88–94. - Режим доступу: http://nbuv.gov.ua/j-pdf/FP_index.htm_2018_1_14.pdf.
Тягло А. В. О стандартах доказательства. Форум права: електрон. наук. фахове вид. 2018. № 1. С. 88–94. URL: http://nbuv.gov.ua/j-pdf/FP_index.htm_2018_1_14.pdf.
Keywords: Філософія. Логіка. Philosophy. Logic. Философия. Логика; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; общелогический стандарт доказательства; стандарт доказательства "вне разумного сомнения"; общая логика; юридическая логика; загальнологічний стандарт доведення; стандарт доведення "поза розумним сумнівом; загальна логіка; юридична логіка; general logic standard of proof; standard of proof "beyond a reasonable doubt"; general logic; legal logic